TANGO—New tracking AlGOrithm for gamma-rays - Tashenov, S.; Gerl, J. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2010)
For spectroscopy, polarimetry and imaging purposes a new γ -ray tracking algorithm has been developed featuring identification of Compton escape events. The rejection of these events results in a significant increase of the Peak/Total ratio. The initial photon energy is restored for these events. Although the energy resolution in the spectrum reconstructed from the escape events is lower than the one from the full-energy events, the Monte-Carlo simulations show that the combined spectrum has an increased detector full-energy efficiency of up to 130% compared to its intrinsic full-energy efficiency. The assumed geometrical origin of the photons is verified event-by-event. This enables separation of photons emitted from a target and from background sources. A linear polarization analysis of the γ -lines can be performed. The efficiency of the algorithm and the Peak/Total ratio depending on the detector properties is discussed along with the proposed optimization schemes. The influence of the intrinsic properties of the scattering process like Compton profile and electron recoiling is discussed as well. The described algorithm deals with single photon events with energies of ≈ 100 keV up to a few MeV.